Analisis Pengaruh Pajak Daerah dan Retribusi Daerah terhadap Pendapatan Asli Daerah Kota Sorong (Studi Kasus Kawasan Wisata Tanjung Kasuari) - Beatriks Mayor; Andrey Maryen; Agnes Eyne Banea (Journal on Education, 2023)
This research aims to analyze the effect of local taxes and regional levies on the original income of the Sorong City area (case study of the Tanjung Kasuari tourist area). Regional Native Income (PAD) is one of the financial resources owned by the regions. Revenue comes from various components such as local taxes, regional levies. This type of research is iresearch research i(field iresearch) idengan i use icualitative proximity, yes, it explains the effect of local taxes and regional levies on the original income of the sorong city area by means of imwa interview, observation, idan itelaah idokumen. This research was carried out at the Regional Revenue Office (DISPENDA) of Sorong City. This research uses the iprimer idan isekunder type of idata iprimer idan. The results of the research show that the contribution of local taxes and regional levies shows that regional taxes and regional levies greatly contribute to regional financial income every year, as evidenced by regional income from regional taxes and regional levies which have always increased over the past five years.